2017
DOI: 10.1590/0103-8478cr20160846
|View full text |Cite
|
Sign up to set email alerts
|

Can vaccines against canine visceral leishmaniasis interfere with the serological diagnostics recommended by the Brazilian Ministry of Health?

Abstract: The objective of the current research was to assess seroconversion in dogs immunized with Leishmune® and Leish Tec® vaccines using rapid chromatographic immunoassay DPP® (Dual Path Platform) (DPP CVL) and enzyme immunoassay (EIE) up to one year after the vaccination protocol. The study sample comprised 28 dogs divided into two groups, each group immunized with an anti-CVL vaccine and clinically monitored for one year through clinical evaluation and laboratory tests. 22 (78.5%) dog were monitored. During the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(14 reference statements)
0
3
0
2
Order By: Relevance
“…In our study we did not evaluate groups of vaccinated dogs, but we believe that the antigens validated in the present study do not detect antibodies from animals vaccinated in the ELISA because they have different epitopes. In the study conducted by Campos et al, 40 dogs vaccinated with Leish-Tec ® were not reagent to DPP and L. major -like-ELISA in the 30, 180 and 360 days after the vaccination protocol.…”
Section: Discussionmentioning
confidence: 97%
“…In our study we did not evaluate groups of vaccinated dogs, but we believe that the antigens validated in the present study do not detect antibodies from animals vaccinated in the ELISA because they have different epitopes. In the study conducted by Campos et al, 40 dogs vaccinated with Leish-Tec ® were not reagent to DPP and L. major -like-ELISA in the 30, 180 and 360 days after the vaccination protocol.…”
Section: Discussionmentioning
confidence: 97%
“…Another aspect worth mentioning is the necessity to verify, prior to the diagnostic test, any possible anti-Leishmania vaccination of the dogs, considering that serological tests may not distinguish between infected and vaccinated animals. (41) Studies have diverged with regard to the results obtained on cross-reactivity: Campos et al (42) recently demonstrated no cross-reactivity of DPP ® CVL for up to 12 months after vaccination of animals in a nonendemic area, whereas Marcondes et al (43) reported that the test can cross-react with vaccine antibodies for up to six months after vaccination. Therefore, such information must be considered before the interpretation of test results.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the main screening and confirmatory tests of canine infection in Brazil are serological, it is possible that the antibody responses elicited by the vaccine interfere with the diagnosis, leading to the inability to distinguish between vaccinated and naturally infected animals. We have recently demonstrated that in a non-endemic area, and up to 1 year after Leish-Tec ® immunization, vaccinated dogs remained negative in the DPP/EIE serological protocol used by the BMH ( 22 , 23 ). On the other hand, the high degree of serological response in rA2 ELISAs observed in previous studies with sera of CVL animals ( 19 21 ) led us to evaluate the potential role of this protein for diagnosis, focusing on possible differences in the responses elicited against immunodominant linear B cell epitopes in a group of Leish-Tec ® vaccinated dogs and in two groups of CVL animals (symptomatic and asymptomatic), naturally infected by L. infantum .…”
Section: Introductionmentioning
confidence: 99%